Effect of Branching Programme on Achievement of Primary Students on L.C.M and H.C.F - Subodh Kumar; Lalima (Indian Journal of Educational Technology, 2024)
Mathematics as a subject is very important and a strong foundation in mathematics ensures better academic performance and a confident personality. A strong foundation of computation skills and understanding of mathematical concepts must be developed during primary school. To achieve this goal the teaching should be individualized so that students can learn, understand, and practice Mathematical concepts at their own pace and using their specific learning styles. Mathematics learning can be made an individualized and joyful experience for students by using the Branching programme as a teaching-learning strategy. The present paper presents the research done to study the impact of the Branching programme on the learning and understanding of two basic concepts of mathematics-L.C.M. and H.C.F. The researcher has developed the branching programme and tested its efficacy of it on students' achievement. The finding shows that the programme was found to be effective for grade five children. Presentation of the concepts of L.C.M and H.C.F. in the form of small frames along with practice questions and providing immediate reinforcement and remedial material proved to be beneficial for the students.content and comes out with a significant sprucing up of student’s achievement.